PAW patrol. Big truck pups [videorecording (DVD)] - Chapman, Keith, 1958-; Kraft, Scott, 1959- (PAW patrol (Television program), 2022)
Get ready for a BIG adventure, BIG rescues, and BIG trucks! Launching from their new Truck Stop HQ, Ryder, the pups, and their new pup-friend Al will take their brand-new Big Trucks out on the road to save the day. The pups team up with Al to save the Adventure Bay Bridge and also stop a flood, plus so much more! Bigger rescues call for bigger rides and a new friend!